Subsistence Economy and The Papua Women Trader Marginalization in The Indonesia-Papua New Guinea Border Trade Region - Erna Ermawaty Chotim (Jurnal Ilmu Sosial Mamangan, 2020)
This study is an analysis about the strategy of governments economic empowerment for Papuans women traders in the district of Muara Tami, located at the border between the West Papua Province and Papua New Guienea. In addition to the problems of low infrastructure development for women traders in border areas, this study found a more complex reality faced by the Papuan women traders that hindered their economic improvement, the competition between the migrant groups who dominated the economic development in their area. By employing a qualitative methods through observation, interviews, and literature study from secondary materials in the field, this study argues that the empowerment agenda for Papuan women traders needs more concerted efforts of affirmative and inclusive policies to protect the economic position of Papuan women traders, rather than a traditional approach of knowledge transfer and skill building alone. This study shows that affirmative and inclusive policies is an important and necessary part of empowerment agenda for Papuan women traders.